KRITIS PENDIDIKAN ISLAM DI KAWASAN ASEAN - Sukari; Taufiq Khoirin; Ikhsan Nur Yahya (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
This study critically examines the development and dynamics of Islamic education policies in the ASEAN region, which is characterized by significant social, political, and cultural diversity. Islamic education across ASEAN countries has evolved through a long historical process influenced by colonial legacies, modernization efforts, and contemporary global challenges such as digitalization and issues related to radicalism. The analysis in this study reveals several crucial policy issues, including curriculum modernization, the integration of religious and general sciences, the persistent dualism in educational systems, technological disparities in digital learning, and identity-based political challenges in minority Muslim communities.Furthermore, this study maps out the future policy directions of Islamic education, emphasizing three main priorities: curriculum modernization, the strengthening of religious moderation, and the advancement of educational digitalization. These priorities serve as a strategic foundation for enhancing the quality of Islamic education in ASEAN, ensuring that it becomes more adaptive, inclusive, and globally competitive.